PERLINDUNGAN WHISTLEBLOWER DALAM KEBIJAKAN HUKUM DI BERBAGAI NEGARA - I Wayan Putu Sucana Aryana (Fakultas Hukum Universitas Ngurah Rai, 2019)
The existence of whistleblowers in the criminal law system in various countries can be seen from the role of whistleblowers in uncovering corruption cases. Some countries define the practice of corruption only in the public sector, but some other countries expand the practice of corruption, namely in the public sector and private sector. These provisions have implications for whistleblower protection. Each country has different policies for the protection of whistleblowers. However, basically, countries provide protection for the security of whistleblowers, both against personal safety, from lawsuits and from discrimination at the career level. Whistleblower protection is regulated by law. The protection system includes physical protection against whistleblowers or non-physical.